Encouraging Interest In Early Language Learning - Haydarova Dildora Komilovna (Genius Journals, 2023)
This study aims to help arouse interest in learning a foreign language as early as possible and to achieve a general motivation in society, among parents and ultimately among children to learn German. Since foreign language acquisition develops slowly, it should start in kindergarten. The DaF offer there should build on the child's curiosity and arouse joy in new learning content (e.g. foreign language sounds).
Keywords: Language; learning